CARICOM and extra-regional export development. - Gonzales, Anthony P. (1990)
Notes that coupled with high levels of effective protection, the small CARICOM market has not facilitated the movement of CARICOM-traded goods into extra-regional market, since producers could not achieve an internationally competitive scale through the development of larger and more specialized firms that could afford the extra cost of going on the international market.